Lateralization of Sucrose Responsiveness and Non-associative Learning in Honeybees - Baracchi, David (Front Psychol, 2018)
Lateralization is a fundamental property of the human brain that affects perceptual, motor, and cognitive processes. It is now acknowledged that left–right laterality is widespread across vertebrates and even some invertebrates such as fruit flies and bees. Honeybees, which learn to associate an odorant (the conditioned stimulus, CS) with sucrose solution (the unconditioned stimulus, US), recall this association better when trained using their right antenna than they do when using their left antenna. Correspondingly, olfactory sensilla are more abundant on the right antenna and odor encoding by projection neurons of the right antennal lobe results in better odor differentiation than those of the left one. Thus, lateralization arises from asymmetries both in the peripheral and central olfactory system, responsible for detecting the CS. Here, we focused on the US component and studied if lateralization exists in the gustatory system of Apis mellifera. We investigated whether sucrose sensitivity is lateralized both at the level of the antennae and the fore-tarsi in two independent groups of bees. Sucrose sensitivity was assessed by presenting bees with a series of increasing concentrations of sucrose solution delivered either to the left or the right antenna/tarsus and measuring the proboscis extension response to these stimuli. Bees experienced two series of stimulations, one on the left and the other on the right antenna/tarsus. We found that tarsal responsiveness was similar on both sides and that the order of testing affects sucrose responsiveness. On the contrary, antennal responsiveness to sucrose was higher on the right than on the left side, and this effect was independent of the order of antennal stimulation. Given this asymmetry, we also investigated antennal lateralization of habituation to sucrose. We found that the right antenna was more resistant to habituation, which is consistent with its higher sucrose sensitivity. Our results reveal that the gustatory system presents a peripheral lateralization that affects stimulus detection and non-associative learning. Contrary to the olfactory system, which is organized in two distinct brain hemispheres, gustatory receptor neurons converge into a single central region termed the subesophagic zone (SEZ). Whether the SEZ presents lateralized gustatory processing remains to be determined.